Cost-Benefit Analysis of Foreign Direct Investment in Indonesia’s Telecommunications Sector Under The New Presidential Policy (2024-2029): A Case Study of PT. Comba Telecom Network Indonesia - Khairillah Masdulhak; Meldasari Said (Journal of World Science, 2025)
With an emphasis on PT. Comba Telecom Network Indonesia, this paper investigates the possible effects of President Prabowo Subianto's new policies on foreign direct investment (FDI) in Indonesia's telecommunications industry. In light of Indonesia's changing regulatory environment, the study assesses the advantages and disadvantages of expanding a business internationally using a Cost-Benefit Analysis (CBA) approach. The results show that although foreign direct investment (FDI) has many advantages, including access to international markets, knowledge transfer, and capital infusion, it also has a number of hazards, including uncertainty in regulations, protectionist measures, and economic nationalism. By offering useful information to investors, decision-makers, and scholarly scholars, the study adds to the larger conversation on foreign direct investment in emerging nations. Under Indonesia's new political leadership, the research's implications go beyond the telecom industry and provide a model for assessing foreign direct investment in other sectors.